Post pandemic: the teaching of chemistry based on socio-scientific controversies in initial engineering students (LACCEI, 2024)
Applied Chemistry is a course that is included in most science majors, especially Engineering. While the teaching of chemistry faces its own difficulties, the pandemic has made the need for adjustments more apparent. The purpose was to replace face-to-face laboratories and facilitate student motivation and engagement. In this sense, the science of education offers psycho-pedagogical strategies that can be effective in helping students learn chemistry, without forgetting the relationship with their future professional performance. Strategies such as Problem-Based or Project-Based Learning (ABP) and the flipped classroom, among others, are teaching-learning methodologies that are applied in the courses with this objective. Any active methodology requires students to be involved in their own learning. This implies a design that considers the cognitive abilities of the student, their self-regulation, and their emotions. So, taking this fact into account, laboratory experiences were carried out at home, appropriate simulations and learning activities by means off situational controversies. All activities were focused on scientific issues, related to the experience and current events of the students. We present a research project, in its initial phase, to examine the effectiveness of including socio-scientific controversies in chemistry undergraduate courses, as a technique to promote meaningful learning and increase student interest.